Percutaneous Closure of Sinus of Valsalva Rupture into the Right Ventricule in a Pediatric Patient: A Case Report - Abdelbaki, Mourad; Touati, M. (International Journal of Innovative Research in Medical Science, 2024)
This case report details a rare instance of an 8-year-old boy with a large sinus of Valsalva rupture in the right ventricle, who underwent successful percutaneous closure. The rarity of this condition in pediatric patients, coupled with the innovative approach to treatment, makes this a significant contribution to pediatric cardiology. The success of procedure highlights the potential of minimally invasive techniques in the management of complex cardiac abnormalities in children.